MicroRNA MiR-21 and MiR-155 are new markers for breast cancer - M. A. Taipov; Z. N. Nikiphorova; K. P. Laktionov; N. E. Levchenko; V. E. Shevchenko (Опухоли женской репродуктивной системы, 2014)
In the cell there is a large class of regulatory molecules referred to as microRNA. Many investigators regard microRNA Mir and Mir-155 as new potential prognostic markers and targets for goal-oriented therapy for breast cancer (BC) these days. MiR-21 and MiR-155 have been found to regulate the metastatic potential of tumor cells and to be differentially expressed in the BC cells. Our review deals with the theoretical prerequisites for and practical results of studying MiR-21 and MiR-155 as potential molecular markers for BC.